2013
DOI: 10.1098/rspb.2013.1398
|View full text |Cite
|
Sign up to set email alerts
|

Attraction to and learning from social cues in fruitfly larvae

Abstract: We examined the use of social information in fruitfly larvae, which represent an ideal model system owing to their robust learning abilities, small number of neurons and well-studied neurogenetics. Focal larvae showed attraction to the distinct odour emanating from food occupied by other larvae. In controlled learning experiments, focal larvae preferred novel odours previously paired with food occupied by other larvae over novel odours previously paired with unoccupied food. When we gave groups of larvae a cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 51 publications
4
77
2
Order By: Relevance
“…Furthermore, larvae and adults learn to prefer odours from food substrates that have been occupied by larvae over odours from unoccupied substrates of similar quality (Durisko and Dukas, 2013;Durisko et al, 2014). Our controlled experiments indicated that the social attraction we documented was not caused by odours from either fruit or yeast.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Furthermore, larvae and adults learn to prefer odours from food substrates that have been occupied by larvae over odours from unoccupied substrates of similar quality (Durisko and Dukas, 2013;Durisko et al, 2014). Our controlled experiments indicated that the social attraction we documented was not caused by odours from either fruit or yeast.…”
Section: Introductionmentioning
confidence: 61%
“…larvae in tests with wild-caught larval and adult fruit flies as well as in experiments using natural fruit (Durisko and Dukas, 2013;Durisko et al, 2014). Volatiles from both L. brevis, which we cultured from our fly population, and L. plantarum, which has been isolated from the Drosophila gut in other studies, were attractive.…”
Section: P=01mentioning
confidence: 99%
See 2 more Smart Citations
“…In the wild, fruit flies search of hospitable habitat with suitable food substrate for mating, egg laying, and rearing larvae. [56] The results from this study imply that the host interaction with the commensal Lactobacillus genus of the gut microbiota can manufacture compounds that serve as cues for the host's searching effort and decision-making. What are these compounds?…”
Section: The Gut Microbiota Impacts Social Behaviormentioning
confidence: 97%